The concept field of Oksana Zabuzhko's short story “Girls”: translatogical aspect - Пєшкова, О. І. (Studia Philologica, 2019)
This article deals with the conceptual field of Oksana Zabuzhko’s short story “Girls” in its original Ukrainian version and English translation. Modern Ukrainian culture integrates in the world one actively, thus sharpening the problem of reception of Ukrainian literature as a main constituent of Ukrainian culture, what leads us to the problem of reception of literary works by Oksana Zabuzhko as a renowned Ukrainian writer. Since “Girls” short story is not paid much attention to in Ukrainian philological studies, the main purpose of this research is to outline the peculiarities of this short story in its Ukrainian and English versions. In the research process the main concepts — the “Darka” and “Effie” concepts — are established and deconstructed, with concepts that constitute them. The links between all the concepts are demonstrated. Also the main differences between the conceptual fields Ukrainian original and English translation of the short story are examined.